Predictably harsh environment is associated with reduced cognitive flexibility in wild food-caching mountain chickadees. (January 2017) - Croston, Rebecca; Branch, Carrie L.; Pitera, Angela M.; Kozlovsky, Dovid Y.; Bridge, Eli S.; Parchman, Thomas L.; Pravosudov, Vladimir V.
Abstract : Cognition is one of the mechanisms underlying behavioural flexibility, but flexibility of cognition itself may vary as a result of trade-offs between the ability to learn new information and the ability to retain old memories. How and when cognitive flexibility is constrained by this trade-off remains poorly understood. We investigated cognitive flexibility in wild food-caching mountain chickadees, Poecile gambeli, at different elevations experiencing different levels of environmental harshness during the nonbreeding season, using a spatial learning and memory reversal paradigm. There were no significant differences in sampling strategies between elevations, but high-elevation chickadees performed worse than low-elevation chickadees on the reversal task, indicating lower cognitive flexibility. Compared to the initial learning task, low-elevation chickadees improved their performance during the reversal task, while high-elevation chickadees performed worse. High-elevation birds inspected previously rewarding locations more frequently than other locations, suggesting that reduced cognitive flexibility is associated with proactive interference. Considering that high-elevation chickadees cache more food and are likely more dependent on these caches than their conspecifics from low elevation, and that chickadees from both elevations use similar sampling strategies, our findings suggest that stronger memories of more caches might interfere with acquisition and retention of new memories. Overall, our results suggest that predictably harsh environments might favour stronger memories at the expense of decreased cognitive flexibility, which is likely driven by increased proactive interference. Highlights: Behavioural flexibility is critical for success in unpredictable environments. Behavioural flexibility might be associated with cognitive trade-offs. Better memory might be associated with more proactive interference. Chickadees in harsh environments show less cognitive flexibility. Lower flexibility is associated with increased proactive interference.